Designing of Rainwater Harvesting Systems Using Drone Images - Hadi Shokati; Mahdi Kouchakzadeh; Aliakbar Noroozi (مهندسی منابع آب, 2021)
Introduction:Iran is facing shortage of water resources due to the climate in which it is located. Since large areas of urban surfaces are Impenetrable streets, the volume of water harvested from these surfaces is significant and can reduce the pressure on water resources and meet a large portion of the non-potable demands, it also prevents the spread of pollution caused by overflows and backlogs in surface water collection facilities and uneconomic increase of their volumes. Materials and Methods:In this paper, the design of rainwater harvesting system from asphalt surfaces was carried out with the aim of meeting part of the green space demand of Tarbiat Modares University faculty of agriculture, using drone images. For this purpose, available data of 22 years of daily precipitation and 761 aerial images were obtained using DJI Phantom3 Professional drone. Then, the digital elevation map of the case study was prepared and to determine the runoff direction, the basin of the area was carried out in the GIS. Reliability percentage and overflow ratios of the tanks were estimated for each level for different tank volumes. Then the optimal volume of each tank was determined using genetic algorithm. Findings:The results showed that due to the topographic status of the faculty street surfaces, the runoff from them could not be collected in one tank, so 4 tanks A, B, C and D with optimized volumes of 6.15, 3.46, 1 and 20 cubic meters were considered in different parts of the street surfaces, respectively. Conclusion:With designing rainwater harvesting systems, a significant amount of rainwater can be stored for non-potable consumption.